Adverse pregnancy outcomes in adolescents and young women with systemic lupus erythematosus: a national estimate - Nicole Ling; Erica Lawson; Emily von Scheven (BMC, 2018)
Abstract Background Pregnant women with systemic lupus erythematosus (SLE) have increased risk of adverse outcomes including disease flare, spontaneous abortion, preeclampsia/eclampsia, premature birth and maternal death. However, pregnancy outcomes among adolescents and young women with SLE have not been well-explored. Our objective was to compare risk of adverse pregnancy outcomes in adolescents and young women with SLE to risk among peers without SLE. Methods We studied the 2000-2011 Nationwide Inpatient Sample (NIS) of the Healthcare Cost and Utilization Project (HCUP) to estimate the prevalence of adverse pregnancy outcomes in women with SLE aged ≤ 21 years at time of delivery. Outcomes were compared to peers without SLE by using multivariate logistic regression to calculate odds ratios and risk differences. Additionally, differences in length of stay and total charges per hospitalization were described. Results There were 8,791,391 unique pregnancies, of which 4002 occurred in young women with SLE. After adjustment for age, race, insurance type and quartile of median income based on patient ZIP code individuals with SLE had increased odds of pre-eclampsia/eclampsia (OR 3.2, 95% CI 2.3-4.6), maternal death (OR 80, 95% CI 10-604), preterm birth (OR 2.7, 95% CI 2-3.7), spontaneous abortion (OR 5.1, 95% CI 2.8-9.6), and induced abortion (OR 30, 95% CI 14-63). The increase in risk among women with SLE was greatest for preterm birth (RD 11%, 95% CI 6-16), pre-eclampsia/eclampsia (RD 9%, 95% CI 5-13), and spontaneous abortion (RD 4%, 95% CI 0.9-6). Risk difference for induced abortion was 2% with 95% CI 0.6-4, while the difference in risk for maternal death did not reach statistical significance (RD 0.4, 95% CI -0.4-1). Conclusions Adolescents and young women with SLE experience increased risk of adverse, pregnancy-specific outcomes as compared to their peers, including pre-eclampsia/eclampsia, maternal death, preterm birth, spontaneous abortion, and induced abortion. Additionally, length of stay and total charges for hospitalization are increased.